Strategic Entrepreneurial Internationalization: A Normative Framework - Autio, Erkko (Strategic Entrepreneurship Journal, 2017)
Research summary Much of the literature on international new ventures (INVs) focuses on early internationalization and views it as an expression of firm‐specific advantages that existed prior to internationalization. This article presents a normative framework that articulates how INVs can leverage internationalization to drive de novo competitive advantage. Drawing on the organizational capability and business model design literatures, the framework of strategic entrepreneurial internationalization (SEI) argues that INVs that adopt an active learning orientation, harness digital infrastructures for cross‐border business model experimentation, encapsulate cross‐border asymmetries in their activity system, and adopt a niche orientation are more likely to succeed in building sustainable competitive advantage. Managerial summary Internationalization can be used strategically to build competitive advantage in the firm and its business model. This is because internationalization exposes the firm to different markets and different competitive environments, therefore providing a potentially rich source of learning and capability development. However, competitive advantage does not automatically follow internationalization: managers of internationalizing new ventures must actively experiment with different business models in different markets to discover ones that work best. The firm also has to make an effort to distill the lessons learned from foreign markets and adjust its business model accordingly. Learning is more effective in narrow niches. Long‐term advantage can be ensured by cementing cross‐border advantages into the cross‐border operation. Copyright © 2017 Strategic Management Society